1994
DOI: 10.1177/016224399401900206
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Challenges to Risk Scientists: An Exploratory Analysis of Survey Data

Abstract: Surveys of almost 1,500 members of three professional societies that do risk analysis (e.g. environmental economics, epidemiology, exposure assessment, industrial hygiene, toxicology) found that 3 in 10 respondents had observed a biased research design, 2 in 10 had observed plagiarism, and 1 in 10 observed data fabrication or falsification. Respondents with many years in risk analysis, business consultants, and industrial hygienists reported the greatest prevalence of misconduct. These respondents perceived po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In the current survey, we asked whether, within the previous academic year, re-spondents had "observed or heard about" faculty engaging in the enumerated behaviors. Although different methods have been used to investigate research misconduct, following Greenberg and Goldberg (1994), among others, we used an indirect approach because meta-analysis has shown that self-report surveys using terms such as "fabricated results" yielded lower percentages of reported misconduct (Fanelli, 2009). Indirect questioning is thus preferred as a means of reducing socialdesirability effects associated with the normative disinclination to personally acknowledge engaging in such conduct and tapping respondents' own beliefs and behaviors (Fisher, 1993).…”
Section: Obtaining the Datamentioning
confidence: 99%
“…In the current survey, we asked whether, within the previous academic year, re-spondents had "observed or heard about" faculty engaging in the enumerated behaviors. Although different methods have been used to investigate research misconduct, following Greenberg and Goldberg (1994), among others, we used an indirect approach because meta-analysis has shown that self-report surveys using terms such as "fabricated results" yielded lower percentages of reported misconduct (Fanelli, 2009). Indirect questioning is thus preferred as a means of reducing socialdesirability effects associated with the normative disinclination to personally acknowledge engaging in such conduct and tapping respondents' own beliefs and behaviors (Fisher, 1993).…”
Section: Obtaining the Datamentioning
confidence: 99%
“…However, these studies have used different methods and asked different questions, so their results have been deemed inconclusive and/or difficult to compare (e.g. [19] , [20] ). A non-systematic review based on survey and non-survey data led to estimate that the frequency of “serious misconduct”, including plagiarism, is near 1% [11] .…”
Section: Introductionmentioning
confidence: 99%
“…13 Greenberg and Goldberg (1994) find that less than 16 percent of environmental and research economists found any utility in any form of government audit or intervention. less relevant.…”
Section: Discussionmentioning
confidence: 99%